2011
DOI: 10.1073/pnas.1111000108
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin–neuraminidase balance confers respiratory-droplet transmissibility of the pandemic H1N1 influenza virus in ferrets

Abstract: A novel reassortant derived from North American triple-reassortant (TRsw) and Eurasian swine (EAsw) influenza viruses acquired sustained human-to-human transmissibility and caused the 2009 influenza pandemic. To identify molecular determinants that allowed efficient transmission of the pandemic H1N1 virus among humans, we evaluated the direct-contact and respiratory-droplet transmissibility in ferrets of representative swine influenza viruses of different lineages obtained through a 13-y surveillance program i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
202
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(214 citation statements)
references
References 33 publications
(39 reference statements)
12
202
0
Order By: Relevance
“…In this study, the ferret model was used to assess the pathogenicity and transmissibility (i.e., the putative zoonotic potential) of four representative contemporary TRSw influenza viruses. Most of these viruses caused mild disease and were inefficiently transmitted through the air, consistent with previous reports in ferrets (20,21) and restricted epidemiology of TRSw influenza viruses in humans (10). However, the Sw/1204 H1N2 virus replicated well in both the ferret upper and lower respiratory tracts, induced severe viral pneumonia, was highly lethal, and was efficiently transmitted via respiratory droplets.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In this study, the ferret model was used to assess the pathogenicity and transmissibility (i.e., the putative zoonotic potential) of four representative contemporary TRSw influenza viruses. Most of these viruses caused mild disease and were inefficiently transmitted through the air, consistent with previous reports in ferrets (20,21) and restricted epidemiology of TRSw influenza viruses in humans (10). However, the Sw/1204 H1N2 virus replicated well in both the ferret upper and lower respiratory tracts, induced severe viral pneumonia, was highly lethal, and was efficiently transmitted via respiratory droplets.…”
Section: Discussionsupporting
confidence: 79%
“…However, the Sw/1204 H1N2 virus replicated well in both the ferret upper and lower respiratory tracts, induced severe viral pneumonia, was highly lethal, and was efficiently transmitted via respiratory droplets. It is noteworthy that ferrets inoculated with the reconstituted 1918 pandemic virus succumbed within 11 d of infection (22), but they did not succumb in this manner to the pH1N1 2009 virus (23) or other genetically related TRSw H1 influenza viruses (21,22). Therefore, our findings suggest that some field isolates from swine may also show zoonotic potential in humans.…”
Section: Discussionmentioning
confidence: 69%
“…In the quail study, we also found that the molecular changes due to mammalian adaptation did not affect the ability of the virus to replicate when both ferret-adapted surface genes were present. It has been reported that a functional balance between HA and NA activity is important for virus replication and transmission (Sun et al, 2013;Yen et al, 2011). An imbalance caused by an avian-origin HA and a mammalian-origin NA may account for the lack of proper replication and transmission…”
Section: Discussionmentioning
confidence: 99%
“…V max reflects the enzyme's catalytic activity. All four European swine influenza viruses showed high K m values, ranging from 281 mM for H3N2 to 492 mM for H1N2, as compared with N1 viruses (Hooper & Bloom, 2013;Ilyushina et al, 2010;Yen et al, 2011). V max values were found to be in the range from 842 U s 21 for H3N2 to 1845 U s 21 for H1pdmN2sw (Table 2).…”
Section: Na Kinetics and Antiviral Susceptibilitymentioning
confidence: 94%
“…It has also been shown that H1N1pdm09 was transmissible amongst ferrets by the AT route, in spite of a much lower NA activity (Yen et al, 2011) compared with that observed for H1pdmN2sw. In the same study, it was suggested that an optimal HA/NA balance is required for AT and it could therefore be speculated that this balance is not optimal in the H1pdmN2sw virus.…”
Section: Na Kinetics and Antiviral Susceptibilitymentioning
confidence: 99%